Image of a Blacksmith in the Traditional World View of Kazakhs in 19th – first Half of 20th Centuries: Образ кузнеца в традиционном мировоззрении казахов XIX – 1-ой пол. ХX вв.:Миф и реальность - Tokhtabayeva, Shaizada (Przegląd Wschodnioeuropejski, 2019)
The article analyzes the multi-faceted personality of the Kazakh blacksmith in ethnotraditional perception compared with the culture of other nations. Such parameters as birth and “magical” diversion of hereditary gift, professional etiquette and the social status of the blacksmith have been considered. The attention has been paid to such qualities of the blacksmith as spiritual self-control, lack of greed, strength and nobility of character. The mentioned is justified by the idea that the moral defects of a master can enter into conflict with his sacred activities which could lead his family to misfortune.